An ultra low power baseband transceiver IC for wireless body area networks - Liu, Xin (2010)
In this paper, we presents a low complexity ultra low power baseband transceiver IC for wireless body area network applications. A specified transceiver architecture for physical layer (PHY) and serial peripheral interface (SPI) realization is proposed and system performance is optimized. Implemented in a 0.18-μm CMOS technology, the baseband chip consumes 240.24 μW for TX mode and 202.34 μW for RX mode when working at a 250 kHz system clock and 1.8V supply.